Teknik Penyiraman Tanaman Menggunakan Mikrokontroler Berbasis Internet of Things - Amsar Yunan; Safriati Safriati; Hermalinda Hermalinda (Journal of Information System Research (JOSH), 2022)
Watering plants is an activity carried out so that the results of plants that are treated to grow well and avoid the water content needed by these plants. Technological developments encourage someone to use a plant watering system that is carried out using the right technology to avoid water content or soil moisture on plants. Moisture content and adjustment to soil contours also make maintenance difficult, because plants have different requirements for water content and humidity for each type of plant. The hollow structure of the soil is also a good place for roots to breathe and plants. Soil is also a habitat for various microorganisms. The purpose of this design is to make it expected that this tool can facilitate plant care in areas that have been planted with sensors that detect soil moisture levels. Watering plants that are still manual becomes plants that are not properly maintained because of the busy time of activity, or types of plants that have special attention both in terms of places that must be cool and water needs that must still be met. The humidity sensor will read the state of dry or wet soil moisture and inform the results of the sensor readings to telegram. The result of the notification sent in the form of this information, the user can find out the state of the plants displayed in his telegram. The test results obtained, it is known that the tool can work according to the needs and specifications. The tool is able to read the moisture content expressed in the dryness of water in the soil and sends the moisture value to a telegram where the pump will water the plants if the soil moisture is below 65% and the pump will turn off if the soil moisture is > 66%.